2022
DOI: 10.3389/fpsyg.2021.795278
|View full text |Cite
|
Sign up to set email alerts
|

Moral Foundations Predict Perceptions of Moral Permissibility of COVID-19 Public Health Guideline Violations in United States University Students

Abstract: In the United States, the COVID-19 pandemic has become highly politicized and highly moralized. The current study explored whether participants’ (N = 118) endorsements of binding (promoting group cohesion) versus individualizing (promoting care for individuals) moral foundations explained partisan differences in views and behaviors regarding COVID-19. Participants completed the Moral Foundations Questionnaire before they indicated how morally permissible they thought it was to violate COVID-19 mandates, report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
(48 reference statements)
3
7
1
3
Order By: Relevance
“…What is more, the Anti-Individualizing cluster were inclined to assess the efficacy of preventive measures more negatively than the Individualizing cluster. Our findings are in line with the research results by Bruchmann and LaPierre (2022), which has shown that values characteristic for the Binding morality are related to a lower level of support for prevention measures such as hand washing, wearing masks and social distancing.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…What is more, the Anti-Individualizing cluster were inclined to assess the efficacy of preventive measures more negatively than the Individualizing cluster. Our findings are in line with the research results by Bruchmann and LaPierre (2022), which has shown that values characteristic for the Binding morality are related to a lower level of support for prevention measures such as hand washing, wearing masks and social distancing.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our hypothesis (H4), we have found that people endorsing Individualizing values tended to assess the efficacy of COVID-19 preventive measures higher than people endorsing Binding values. Presumably, the Individualizing values are linked to perceiving serious violations of COVID-19 as less morally acceptable, possibly because severe violations of the COVID-19 guidelines could be viewed as harmful (Bruchmann & LaPierre, 2022) and probably also unfair to society and its members. Answering our second research question (RQ2), we found that people endorsing Binding moral values were inclined to assess all preventive measures (except for frequent disinfection of hands and surfaces) more negatively than the Individualizing and Generally Moral clusters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations